Extent of glaucomatous damage on the first presentation - Sayali Bhedasgaonkar; Snehal U Nadkarni (Oman Journal of Ophthalmology, 2023)
AIM: The aim is to determine the magnitude of glaucomatous damage in the asymptomatic subjects identified with primary glaucoma for the first time and thus to evaluate the significance and efficacy of screening measures for glaucoma. MATERIALS AND METHODS: An observational retrospective cohort study of 100 asymptomatic patients of age more than 40 years, diagnosed with and under treatment for primary glaucoma was performed. Patients were categorized into having early, moderate, and severe glaucoma, according to standard automated perimetry (SAP) mean deviation (MD) in the worse eye (<−6, −6 to −12 and >−12 dB, respectively). Risk factors were correlated with the severity of glaucoma at presentation and statistically analyzed. RESULTS: About 32%, 33%, and 35% of patients were found to have early, moderate, and severe stages of glaucoma with average MD of −3.51 ±1.53, −8.65 ±1.64, −17.15 ± 5.13 on SAP, respectively. The association of risk factors such as age (P = 0.006) and glaucoma awareness (P = 0.044) with the severity of glaucoma was statistically significant. There was no direct statistical correlation found between gender, history of diabetes mellitus, family history of glaucoma, intraocular pressure, central corneal thickness, the angle width, and the severity of glaucoma in our study. CONCLUSION: Majority of cases with primary glaucoma show no symptoms until advanced irreversible stages. Early screening and proper treatment are the only ways to halt its progression. In spite of available facilities, 68% of patients in our study were found to have moderate-to-severe stages of glaucoma. This indicates that our screening measures should reach the masses at the primary level, with a focus on awareness programs.